N2 Binding to the FeMo‐Cofactor of Nitrogenase1. Issue 1 (1st August 2014) - Hallmen, Philipp P.; Kästner, Johannes
Abstract Nitrogenase converts gaseous dinitrogen into biologically accessible ammonia. The binding of N2 to a reduced and protonated form of the FeMo‐cofactor of nitrogenase including its central carbon ligand was investigated by means of density functional calculations. It was found the central ligand to stabilize the cluster. N2 can associate to iron or molybdenum with iron being the preferred binding site. While endo and exo binding modes were investigated the exo modes are more stable. Implications on the mechanism of N2 reduction are discussed.